2013
DOI: 10.1039/c3sm50869b
|View full text |Cite
|
Sign up to set email alerts
|

Nonaqueous ionic liquid microemulsions of 1-butyl-3-methylimidazolium tetrafluoroborate, toluene and ethanol

Abstract: The phase behavior of the ternary system consisting of the hydrophilic ionic liquid (IL) 1-butyl-3-methylimidazolium tetrafluoroborate (bmimBF 4 ), toluene and ethanol was investigated. Single-phase microemulsion and multiphase regions were observed in the ternary phase diagram. To the best of our knowledge, this is the first report on nonaqueous IL microemulsions prepared in the absence of traditional surfactants. The microstructures and structural transitions of the microemulsion system were investigated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 43 publications
8
37
0
Order By: Relevance
“…Similarly, the diffusion coefficient of oil D o also increase monotonically as the concentration of oil becomes higher, but D o is more continuous than D w . In summary, the response of SCFME diffusion to concentration is consistent with those observed for SBMEs and SFMEs from electrical conductivity and cyclic voltammetry studies.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Similarly, the diffusion coefficient of oil D o also increase monotonically as the concentration of oil becomes higher, but D o is more continuous than D w . In summary, the response of SCFME diffusion to concentration is consistent with those observed for SBMEs and SFMEs from electrical conductivity and cyclic voltammetry studies.…”
Section: Resultssupporting
confidence: 83%
“…Besides structures, many other properties such as surface tension, diffusion, conductivity, and evaporation rate undergo a progressive change when the concentration ratio of the water/oil mixture varies. To test whether the SCFME in our simulation has such feature, we calculated the diffusion coefficient of water D w as a function of M w .…”
Section: Resultsmentioning
confidence: 99%
“…The uncertainty in locating the boundaries of different subregions is estimated to be less than 10%. The microstructures and structural transition observed herein are similar to those reported for other SFMEs 2,7,9,[13][14][15]19,21 and SBMEs. 33,35,[38][39][40]…”
Section: Structures and Structural Transition Of Microemulsionssupporting
confidence: 86%
“…Subsequently, the formation of SFMEs was conrmed in some surfactant-free ternary systems. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] The structures, properties, and formation mechanism of SFMEs have been investigated. 1,2,[22][23][24] It has been preliminarily demonstrated that the structures and properties of SFMEs are similar to those of traditional SBMEs to some extent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation